An assessment of the implementation of one-town-one product (OTOP) program in the province of Antique. - Escanillas, Hazel Mae Ardon
This study described and assessed the implementation of One-Town-One-Product (OTOP) Program in the Province of Antique. Specifically, this study described the nature of OTOP products and services in the municipalities of Antique; the nature of government support to the OTOP Program in every municipality; the impacts of OTOP to income and employment of the participants; identified the problems encountered in the implemetation of the program; determined the benefits derived by the government; and suggested policies for the improvement of the program. Methods used to collect necessary data for the assessment of the OTOP Program were structured interview schedule, key informant interview and focus group discussion. Muscovado sugar, fruits and vegetables, dairy products, tourism services, handicrafts, loom woven products, fish and fish preparatins and seaweeds are theproducts and services or the OTOP identity. The local government unit identifies the specific product or service and makes available all forms of assistance. The availability of the raw materials was identified as the primary basis in choosing the OTOP identity. Insufficient knowledge about the OTOP Program became an important issue to some of the coordinators who were just employed. Lack of financial support from the government was the prominent hindrance being faced by most of the municipalities in terms of sustaining the program. It is recommended for the provincial government to find more effective ways to link the OTOP Program with available assistance in terms of financial, technological and entrepreneurial trainings.